Dental decision‐making under general anesthesia for patients with disabilities: A qualitative study. (13th July 2021) - McGeown, Danielle; Mac Giolla Phadraig, Caoimhin; Whelehan, Dale; Nunn, June H.
Abstract: Aims: This paper explores the variables which influence decision‐making processes in dentists providing dental care for people with disabilities under general anesthesia (GA). Methods: Face‐to‐face semi‐structured interviews were undertaken on a purposive sample. Audio recordings were transcribed and checked for accuracy. Using thematic content analysis methods open codes were developed inductively. Codes were analyzed further by three authors adopting a deductive approach, leading to final coding, sorting and themes, subtheme and framework development. Results: Three themes emerged. The first theme explored Shared Decision Making, or lack thereof, as it influenced clinical reasoning. The second (Systematic, Analytical) and third (Intuition, and heuristics) themes explored features of clinical judgment as considered under dual process theory. Dentists primarily used intuitive decision‐making processes and heuristic styled processes (or cognitive mental frames) assisted in intuition to extract teeth, without engaging type 2 processes. Conclusion: The dentists experience subtle modifiers to their decision‐making that ultimately promote extraction of teeth under GA for people with disabilities. Bias training, simulation and post‐hoc reflection are examples of recommendations which may be used to improve decision‐making in this area.